Substantiation, directions and results of using whey processed products in ice cream production - P. B. Sitnikova; N. V. Kazakova (Пищевые системы, 2024)
The deficiency of protein is an important global problem. Whey, as a by-product of the production of cheese and cottage cheese, can be an additional source of protein. The feasibility of using whey for food purposes due to its composition and biological value is substantiated in the review. Besides, the usage of whey for food purposes reduces threat of environmen‑tal pollution existing when disposing it into the sewer. The aim of the article was to collect, analyze and summarize data on the use of whey and products of its processing in the technology of ice cream and whipped frozen desserts. The analysis of the data of the International Dairy Federation (IDF) on the global volumes of milk whey production as well as the amount of high-value protein, to which they are equivalent, is given. The modern world experience in processing technologies of whey and the product assortment made with its usage has been analyzed. Attention is concentrated on the characteristics and properties of whey processed products (concentrates, isolates, milk hydrolysates, first of all, whey proteins) and micellar casein. The research experience in studying the possibility of their use in the production of ice cream and other foods is assessed and summarized. The influence of these products on the technological, structural-mechanical, microstructural and organoleptic characteristics of ice cream and on its biological value is considered. The presence of positive and negative experience in the usage of dairy proteins, including whey proteins, on the consumer characteristics of frozen food is noted. The necessity of more detailed study of results of using each particular source of milk protein in relation to different types of ice cream and whipped frozen desserts is substantiated.